Short commentary on marine productivity at Arctic shelf breaks: upwelling, advection and vertical mixing - A. Randelhoff; A. Randelhoff; A. Sundfjord (Ocean Science, 2018)
The future of Arctic marine ecosystems has received increasing attention in recent years as the extent of the sea ice cover is dwindling. Although the Pacific and Atlantic inflows both import huge quantities of nutrients and plankton, they feed into the Arctic Ocean in quite diverse regions. The strongly stratified Pacific sector has a historically heavy ice cover, a shallow shelf and dominant upwelling-favourable winds, while the Atlantic sector is weakly stratified, with a dynamic ice edge and a complex bathymetry. We argue that shelf break upwelling is likely not a universal but rather a regional, albeit recurring, feature of <q>the new Arctic</q>. It is the regional oceanography that decides its importance through a range of diverse factors such as stratification, bathymetry and wind forcing. Teasing apart their individual contributions in different regions can only be achieved by spatially resolved time series and dedicated modelling efforts. The Northern Barents Sea shelf is an example of a region where shelf break upwelling likely does not play a dominant role, in contrast to the shallower shelves north of Alaska where ample evidence for its importance has already accumulated. Still, other factors can contribute to marked future increases in biological productivity along the Arctic shelf break. A warming inflow of nutrient-rich Atlantic Water feeds plankton at the same time as it melts the sea ice, permitting increased photosynthesis. Concurrent changes in sea ice cover and zooplankton communities advected with the boundary currents make for a complex mosaic of regulating factors that do not allow for Arctic-wide generalizations.